2018 Annual Scientific Gender Conference - Pyburn, Rhiannon (CGIAR Collaborative Platform on Gender Research, 2018)
Presented by Rhiannon Pyburn (Gender Platform/KIT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.